Implementation of Differentiated Learning Approach to Improve Social Skills and Student Learning Outcomes - Supriati Supriati; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
This study aims to explore the impact of differentiated instruction on students’ social skills and academic achievement at SDN 3 Kemawi. The research was motivated by the diverse characteristics of students and the need for responsive teaching approaches to accommodate these differences. A qualitative descriptive method was employed, with data collected through observation, interviews, documentation, as well as pre-tests and post-tests. The research subjects were 3rd and 5th-grade students, representing lower and upper elementary levels. The findings indicate that the implementation of differentiated instruction effectively enhanced students’ social skills, as reflected in the increased number of students categorized as “Very Good” and the decreased number in the “Fair” category. Moreover, there was a significant improvement in academic achievement, with the average score in 3rd grade increasing from 81.24 to 86.88, and in 5th grade from 80.84 to 88.00. Factors such as students’ basic literacy skills and social environment were found to influence the success of the instructional model. These results suggest that differentiated instruction, supported by the right media, can positively contribute to students' academic and social development.